Enhancing surface segregation with cyclic polymer additives: A facile approach to surface modification - Kang, Seungmin; Koh, Won-Gun; Joung, Yoon Ki (Pergamon Press Ltd., 2024)
The preferential surface segregation of one component of a polymer blend has been used for the controlled modification of the surface properties. Unlike other modification methods, this technique is simple and does not require any complex modeling or additional processing steps for surface modification. Most surface segregation studies are based on the interaction between the chain ends of the additive and bulk polymer at the surface. However, additives with cyclic topologies without chain ends have not been used. In this study, an additive platform with cyclic topology without a chain end was designed for surface modification. A series of cyclic additives were synthesized via ring-expansion cationic polymerization. X-ray photoelectron spectroscopy analysis of the cyclic polymer additive showed approximately 1.5 times higher surface segregation than the linear polymer when blended with polyurethane. In addition, the surface segregation behavior depending on the molecular weight and pendant length of the cyclic polymer additive was investigated. Moreover, the monomer, allyl vinyl ether, enabled the addition of functional groups to the cyclic additive and the addition of perfluoroalkyl pendant groups was performed, revealing a promising antifouling effect in the adsorption of a plasma protein. The high performance and versatility of the cyclic architectural polymer additives extend the scope of the surface segregation field and can replace existing biomedical coatings.